A hydrophilic fibrous silver dressing and a method of making the same
Patent Information
- Application Number
- CN202611114503.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-27
AI Technical Summary
[0004]本发明的目的在于:提供了一种亲水性纤维银敷料及其制备方法,解决了亲水性纤维银敷料应用于高渗伤时,吸液溶胀后很难维持适度的湿气透过率,亲水性纤维会很快出现渗漏液的问题
1.本发明一种亲水性纤维银敷料以并列型双组分纤维为吸收层的核心材料,其中,巯基化海藻酸钙海藻酸钙纤维吸湿膨胀,将大量伤口渗出液保持在凝胶结构中,能够阻止伤口渗出液向四周流动和对健康组织的浸渍;第二组分纤维具有温敏性,在创面体温下发生体积收缩并转变为疏水态;吸液膨胀与温敏收缩产生的界面应力差驱动纤维发生弯曲变形,并具有局部疏水区域,吸收层能够维持局部的孔隙结构,可以维持适度的湿气透过率,解决了现有亲水性纤维敷料吸液后溶胀导致孔隙大范围闭合、透气性显著丧失的问题,与现有单组分吸湿膨胀纤维相比,本发明吸收层的吸液至边缘渗漏液的速度相对较慢;
Smart Images

Figure CN122624711B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medical dressing processing technology, and relates to a hydrophilic fiber silver dressing and its preparation method. Background Technology
[0002] Hydrophilic fiber silver dressings are soft, sterile nonwoven pads or strips of dressing currently composed primarily of sodium carboxymethyl cellulose and silver ions. The silver in the dressing kills wound bacteria within the dressing and helps form an antimicrobial barrier to protect the wound bed. The dressing absorbs a large amount of wound exudate, creating a moist gel environment that adheres to the wound surface, controlling wound bacteria to aid the body's healing process and helping to reduce the risk of wound infection.
[0003] However, after absorbing liquid, the hydrophilic fiber silver dressing swells, and the volume expands to fill the pores, which reduces air permeability and may even form a dense gel layer. This is especially true for high exudative wounds, where the amount of exudate is large and the hydrophilic fiber silver dressing swells significantly after absorbing liquid, resulting in poor air permeability. Poor air permeability can easily lead to obstructed water evaporation, and the hydrophilic fiber silver dressing will quickly become saturated with liquid, causing leakage from the edges of the dressing. Summary of the Invention
[0004] The purpose of this invention is to provide a hydrophilic fiber silver dressing and its preparation method, which solves the problem that when hydrophilic fiber silver dressing is applied to hyperpermeable wounds, it is difficult to maintain a moderate moisture permeability after absorbing liquid and swelling, and the hydrophilic fibers will quickly leak liquid.
[0005] The technical solution adopted in this invention is as follows: A hydrophilic fiber silver dressing includes a silver ion antibacterial layer, an absorbent layer, and a support layer bonded together sequentially from the inside out. The silver ion antibacterial layer is bonded to the center of the inner surface of the absorbent layer, and the coverage area of the silver ion antibacterial layer is smaller than the inner surface area of the absorbent layer. The outer surface of the absorbent layer is bonded to the inner surface of the support layer, and the coverage area of the absorbent layer is smaller than the inner surface area of the support layer. The absorbent layer includes parallel bicomponent fibers, which include a first component fiber and a second component fiber arranged in parallel. The first component fiber includes thiolated calcium alginate; The second component fiber comprises a polymer obtained by polymerizing N-isopropylacrylamide, acrylic acid, and maleimide polyethylene glycol methacrylate; wherein the mass ratio of N-isopropylacrylamide, acrylic acid, and maleimide polyethylene glycol methacrylate is (88~92):(8~12):(1.5~3).
[0006] Furthermore, the silver ion antibacterial layer comprises the following components in parts by weight: 1-1.5 parts PVP-modified silver nanoparticles, 6-8 parts thiolated sodium alginate, 2-4 parts glycerol, and 88-90 parts deionized water; Among them, the PVP-modified silver nanoparticles are prepared by using PVP K30 and 0.05 M silver nitrate in a molar ratio of 2.5:1 as the main raw materials and ethylene glycol as the solvent at 80℃ to obtain PVP-modified silver nanoparticles with a particle size of 5~15nm. The mercaptomodified sodium alginate has a mercapto molar substitution degree of 20% and a purity of >95%.
[0007] Furthermore, the support layer comprises the following components in parts by weight: 100 parts of isocyanate-terminated polyurethane prepolymer and 15-20 parts of hydroxystearic acid modified attapulgite.
[0008] Furthermore, the isocyanate-terminated polyurethane prepolymer was prepared by reacting pure MDI and polycarbonate diol (PCDL 2000) in a molar ratio of 2.2:1. The hydroxystearic acid modified attapulgite was prepared by the following method: attapulgite was soaked in 5% HCl hydrochloric acid, stirred for 2 hours, centrifuged, washed until neutral, and dried to obtain acid-treated attapulgite; 100 parts of acid-treated attapulgite were dispersed in anhydrous ethanol, and 15 parts of 12-hydroxystearic acid and p-toluenesulfonic acid were added. The amount of p-toluenesulfonic acid added was 1% of the total mass of acid-treated attapulgite and hydroxystearic acid. The mixture was refluxed and stirred at 80°C for 4 hours. After filtration, washing, drying, and grinding, hydroxystearic acid modified attapulgite was obtained.
[0009] Further, the support layer is prepared by the following method: 100 parts of isocyanate-terminated polyurethane prepolymer are dissolved in a mixed solvent of 300-400 parts DMF and 100-150 parts THF, 15-20 parts of hydroxystearic acid modified attapulgite and 0.05-0.1 parts of organic bismuth catalyst are added, the mixture is stirred at high speed and dispersed evenly, and then degassed under vacuum to obtain a spinning solution; the spinning solution is electrospun to obtain a fiber membrane, and the fiber membrane is cured by gradient heating and then exposed to a water vapor environment with a relative humidity of 85%-90%, treated at 40°C for 1-2 hours, and then vacuum dried to obtain a support layer with a thickness of 30-40 μm; The gradient change of the fiber membrane during gradient heating curing is as follows: curing at 60℃ for 2 hours, then at 80℃ for 2 hours, and finally at 100℃ for 1 hour.
[0010] Furthermore, a pressure-sensitive adhesive layer is also provided on the inner surface of the support layer, and the pressure-sensitive adhesive layer is uniformly disposed around the outer edge of the support layer, with the absorbent layer surrounded inside the pressure-sensitive adhesive layer; the pressure-sensitive adhesive layer is medical polyacrylate pressure-sensitive adhesive.
[0011] Furthermore, the cross-sectional area ratio of the first component fiber and the second component fiber is 45:55.
[0012] The method for preparing a hydrophilic fiber silver dressing includes the following steps: S1. Preparation of parallel bicomponent fibers: The first component spinning solution and the second component spinning solution are wet-spun through a parallel spinneret; the two spinning solutions converge and are extruded in parallel at the spinneret outlet, and the extruded fibers are solidified in a 3% calcium chloride aqueous solution coagulation bath at 50°C. After solidification, the fibers are stretched, washed with deionized water, and vacuum dried at 45°C to obtain parallel bicomponent fibers. The cross-sectional area ratio of the first component fiber to the second component fiber in the parallel bicomponent fibers is 45:55. First component spinning solution: Dissolve sodium thiolated alginate with a thiol content of 500 μmol / g in water to prepare a sodium thiolated alginate solution with a mass fraction of 5%~7%, which is the first component spinning solution; The second component spinning solution: N-isopropylacrylamide, acrylic acid, and maleimide polyethylene glycol methacrylate are dissolved in water at a mass ratio of (88~92):(8~12):(1.5~3) to form a monomer reaction solution. N,N'-methylenebisacrylamide (a crosslinking agent) and potassium persulfate-sodium bisulfite (an initiator) are added to the monomer reaction solution to prepare the second component spinning solution. The amount of crosslinking agent is 1% of the total monomer mass, and the amount of initiator is 0.3% of the total monomer mass. S2. Process the parallel bicomponent fibers obtained in step S1 into fibers with a unit area mass of 100~120 g / m². 2 The nonwoven fabric forms an absorbent layer with a thickness of 0.25mm-0.35mm; S3. Preparation of silver ion antibacterial layer: Dissolve thiolated sodium alginate in deionized water, add glycerol and PVP-modified silver nanoparticles, mix evenly to obtain a dispersion; apply the dispersion to the central area of the inner surface of the absorbent layer in step S2 by spraying, and dry at 35°C in the dark to form silver ion antibacterial layer. S4. Composite the support layer and the absorbent layer: The outer surface of the absorbent layer with the silver ion antibacterial layer is bonded to the inner surface of the support layer by discrete dotted acrylic pressure-sensitive adhesive. The coverage area of the absorbent layer is smaller than the inner surface area of the support layer. After drying at 45°C for 30 minutes, it is die-cut, packaged and sterilized at low temperature with ethylene oxide to obtain the hydrophilic fiber silver dressing.
[0013] Furthermore, the silver content in a single hydrophilic fiber silver dressing accounts for 0.08% of the total mass of the hydrophilic fiber silver dressing.
[0014] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. This invention discloses a hydrophilic fiber silver dressing with parallel bicomponent fibers as the core material of the absorbent layer. The first component, thiolized calcium alginate, absorbs moisture and expands, retaining a large amount of wound exudate within a gel structure, preventing the exudate from flowing outwards and soaking into healthy tissue. The second component fiber is thermosensitive, shrinking in volume and transforming into a hydrophobic state at the wound's body temperature. The interfacial stress difference between the liquid absorption expansion and thermosensitive shrinkage drives the fibers to bend and deform, creating localized hydrophobic regions. The absorbent layer maintains a localized pore structure, ensuring adequate moisture permeability. This solves the problem of existing hydrophilic fiber dressings swelling after liquid absorption, leading to large-scale pore closure and significant loss of breathability. Compared to existing single-component moisture-absorbing and expanding fibers, the absorbent layer of this invention absorbs liquid to the edge at a relatively slower rate of leakage. 2. In this invention, the first component fiber and the second component fiber are connected by chemical bonds through thiol groups and maleimide. The two component fibers are firmly connected and are not easy to separate or detach, which can achieve stable deformation of the whole fiber. Attached Figure Description
[0015] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort, wherein: Figure 1 This is a flowchart of a method for preparing a hydrophilic fiber silver dressing according to the present invention; Figure 2 This is a physical image of the invention. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention; that is, the described embodiments are merely some embodiments of the invention, and not all embodiments. The components of the embodiments of the invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0017] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.
[0018] It should be noted that relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0019] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0020] In the following embodiments, a hydrophilic fiber silver dressing of the present invention includes a silver ion antibacterial layer, an absorbent layer, and a support layer bonded together sequentially from the inside to the outside; the silver ion antibacterial layer is bonded to the center of the inner surface of the absorbent layer and the coverage area of the silver ion antibacterial layer is smaller than the inner surface area of the absorbent layer; the outer surface of the absorbent layer is bonded to the inner surface of the support layer and the coverage area of the absorbent layer is smaller than the inner surface area of the support layer; the absorbent layer includes parallel bicomponent fibers, and the parallel bicomponent fibers include a first component fiber and a second component fiber arranged in parallel; The first component fiber includes thiolated calcium alginate; The second component fiber comprises a polymer obtained by polymerizing N-isopropylacrylamide, acrylic acid, and maleimide polyethylene glycol methacrylate; wherein the mass ratio of N-isopropylacrylamide, acrylic acid, and maleimide polyethylene glycol methacrylate is (88~92):(8~12):(1.5~3).
[0021] In the following embodiments, the silver ion antibacterial layer comprises the following components in parts by weight: 1.5 parts PVP-modified silver nanoparticles, 7 parts thiolated sodium alginate, 3 parts glycerol, and 89 parts deionized water; Among them, the PVP-modified silver nanoparticles are prepared by using PVP K30 and 0.05 M silver nitrate in a molar ratio of 2.5:1 as the main raw materials and ethylene glycol as the solvent at 80℃ to obtain PVP-modified silver nanoparticles with a particle size of 5~15nm. The mercaptomodified sodium alginate has a mercapto molar substitution degree of 20% and a purity of >95%.
[0022] In the following embodiments, the support layer comprises the following components in parts by weight: 100 parts of isocyanate-terminated polyurethane prepolymer and 15-20 parts of hydroxystearic acid modified attapulgite.
[0023] In the following examples, the isocyanate-terminated polyurethane prepolymer was prepared by reacting pure MDI and polycarbonate diol (PCDL 2000) in a molar ratio of 2.2:1. The hydroxystearic acid modified attapulgite was prepared by the following method: attapulgite was soaked in 5% HCl hydrochloric acid, stirred for 2 hours, centrifuged, washed until neutral, and dried to obtain acid-treated attapulgite; 100 parts of acid-treated attapulgite were dispersed in anhydrous ethanol, and 15 parts of 12-hydroxystearic acid and p-toluenesulfonic acid were added. The amount of p-toluenesulfonic acid added was 1% of the total mass of acid-treated attapulgite and hydroxystearic acid. The mixture was refluxed and stirred at 80°C for 4 hours. After filtration, washing, drying, and grinding, hydroxystearic acid modified attapulgite was obtained.
[0024] In the following embodiments, the support layer was prepared by the following method: 100 parts of isocyanate-terminated polyurethane prepolymer were dissolved in a mixed solvent of 350 parts DMF and 120 parts THF, 18 parts of hydroxystearic acid-modified attapulgite and 0.08 parts of organic bismuth catalyst were added, and the mixture was stirred at high speed to disperse evenly. Vacuum degassing was then performed to obtain a spinning solution. The spinning solution was electrospun to obtain a fiber membrane. After the fiber membrane was cured by gradient heating, it was exposed to a water vapor environment with a relative humidity of 85%, treated at 40°C for 1.5 hours, and then vacuum dried to obtain a support layer with a thickness of 35 μm. The gradient change of the fiber membrane during gradient heating curing is as follows: curing at 60℃ for 2 hours, then at 80℃ for 2 hours, and finally at 100℃ for 1 hour.
[0025] In the following embodiments, a pressure-sensitive adhesive layer is further disposed on the inner surface of the support layer, the pressure-sensitive adhesive layer is uniformly disposed around the outer edge of the support layer, and the absorbent layer is surrounded inside the pressure-sensitive adhesive layer; the pressure-sensitive adhesive layer is a medical polyacrylate pressure-sensitive adhesive.
[0026] In the following embodiments, the cross-sectional area ratio of the first component fiber and the second component fiber is 45:55.
[0027] In the following embodiments, such as Figure 1 As shown, a method for preparing a hydrophilic fiber silver dressing includes the following steps: S1. Preparation of parallel bicomponent fibers: The first component spinning solution and the second component spinning solution are wet-spun through a parallel spinneret; the two spinning solutions converge and are extruded in parallel at the spinneret outlet, and the extruded fibers are solidified in a 3% calcium chloride aqueous solution coagulation bath at 50°C. After solidification, the fibers are stretched, washed with deionized water, and vacuum dried at 45°C to obtain parallel bicomponent fibers. The cross-sectional area ratio of the first component fiber to the second component fiber in the parallel bicomponent fibers is 45:55. First component spinning solution: Dissolve sodium thiolated alginate with a thiol content of 500 μmol / g in water to prepare a 6% (w / w) sodium thiolated alginate solution, which is the first component spinning solution; The second component spinning solution: N-isopropylacrylamide, acrylic acid, and maleimide polyethylene glycol methacrylate are dissolved in water at a mass ratio of (88~92):(8~12):(1.5~3) to form a monomer reaction solution. N,N'-methylenebisacrylamide (a crosslinking agent) and potassium persulfate-sodium bisulfite (an initiator) are added to the monomer reaction solution to prepare the second component spinning solution. The amount of crosslinking agent is 1% of the total monomer mass, and the amount of initiator is 0.3% of the total monomer mass. S2. Process the parallel bicomponent fibers obtained in step S1 into fibers with a unit area mass of 100~120 g / m². 2 The nonwoven fabric forms an absorbent layer with a thickness of 0.25mm-0.35mm; S3. Preparation of silver ion antibacterial layer: Dissolve thiolated sodium alginate in deionized water, add glycerol and PVP-modified silver nanoparticles, mix evenly to obtain a dispersion; apply the dispersion to the central area of the inner surface of the absorbent layer in step S2 by spraying, and dry at 35°C in the dark to form silver ion antibacterial layer. S4. Composite the support layer and the absorbent layer: The outer surface of the absorbent layer with the silver ion antibacterial layer is bonded to the inner surface of the support layer by discrete dotted acrylic pressure-sensitive adhesive. The coverage area of the absorbent layer is smaller than the inner surface area of the support layer. After drying at 45°C for 30 minutes, it is die-cut, packaged and sterilized at low temperature with ethylene oxide to obtain the hydrophilic fiber silver dressing.
[0028] In the following examples, the silver content in one hydrophilic fiber silver dressing is 0.08% of the total mass of the hydrophilic fiber silver dressing.
[0029] The specific implementation method is as follows: Example 1:
[0030] A hydrophilic fiber silver dressing provided in a preferred embodiment of the present invention is prepared by the following method: Step 1: Preparation of side-by-side bicomponent fibers First component spinning solution: Dissolve sodium thiosulfate with a thiol content of 500 μmol / g in deionized water to prepare a 6% mass fraction solution, which is the first component spinning solution; Second component spinning solution: Dissolve 90g of N-isopropylacrylamide, 10g of acrylic acid, and 2g of maleimide polyethylene glycol methacrylate in water, add 1.02g of crosslinking agent N,N'-methylenebisacrylamide, 0.15g of initiator potassium persulfate and 0.15g of sodium bisulfite, stir evenly to obtain the second component spinning solution; Parallel spinning: The first and second component spinning solutions are wet-spun through parallel spinnerets; the two spinning solutions converge and are extruded in parallel at the spinneret outlet. The extruded fibers enter a coagulation bath containing 3% calcium chloride aqueous solution and are solidified at 50°C. After solidification, the fibers are drawn, washed with deionized water, and vacuum dried at 45°C to obtain parallel bicomponent fibers. The cross-sectional area ratio of the first and second component fibers in the parallel bicomponent fibers is 45:55.
[0031] Step 2: Preparation of the absorption layer The side-by-side bicomponent fibers are processed to a basis weight of 110 g / m². 2 The nonwoven fabric forms an absorbent layer with a thickness of 0.3 mm.
[0032] Step 3: Preparation of the silver ion antibacterial layer Dissolve 7g of thiolated sodium alginate in 89g of deionized water, add 3g of glycerol and 1.5g of PVP-modified silver nanoparticles, stir evenly to obtain a dispersion; apply the dispersion to the central area of the inner surface of the absorbent layer in step S2 by spraying, and dry at 35°C in the dark to form a silver ion antibacterial layer; the silver content in one hydrophilic fiber silver dressing accounts for 0.08% of the total mass of the hydrophilic fiber silver dressing.
[0033] Step 4: Preparation of the support layer 100g of isocyanate-terminated polyurethane prepolymer was dissolved in a mixed solvent of 350g DMF and 120g THF. 18g of hydroxystearic acid-modified attapulgite and 0.08g of organic bismuth catalyst were added, and the mixture was stirred at high speed to disperse it evenly. Vacuum degassing was then performed to obtain a spinning solution. The spinning solution was electrospun to obtain a fiber membrane. After gradient heating curing, the fiber membrane was exposed to a water vapor environment with a relative humidity of 85% and treated at 40℃ for 1.5 hours. After vacuum drying, a support layer with a thickness of 35μm was obtained. The gradient change of the fiber membrane during gradient heating curing was as follows: curing at 60℃ for 2 hours, then at 80℃ for 2 hours, and finally at 100℃ for 1 hour.
[0034] Step 5: Dressing Assembly The outer edge of the inner surface of the support layer is pre-coated with medical-grade polyacrylate pressure-sensitive adhesive for skin adhesion. The middle area of the inner surface of the support layer is bonded to the outer surface of the absorbent layer with a silver ion antibacterial layer via discrete dots of acrylic pressure-sensitive adhesive. After drying at 45°C for 30 minutes, it is die-cut, packaged, and sterilized with ethylene oxide to obtain a hydrophilic fiber silver dressing with a silver content of 0.08% of the total mass of the hydrophilic fiber silver dressing. The actual product prepared within the scope of Example 1 is shown below. Figure 2 As shown.
[0035] Example 2:
[0036] This embodiment differs from Example 1 in that the second component spinning solution is prepared by dissolving 88g of N-isopropylacrylamide, 8g of acrylic acid, and 1.5g of maleimide polyethylene glycol methacrylate in water, adding 0.98g of crosslinking agent N,N'-methylenebisacrylamide, 0.15g of initiator potassium persulfate, and 0.15g of sodium bisulfite, and stirring until homogeneous to obtain the second component spinning solution. The rest is the same as in Example 1.
[0037] The second component fiber comprises a polymer obtained by polymerizing N-isopropylacrylamide, acrylic acid, and maleimide polyethylene glycol methacrylate; wherein the mass ratio of N-isopropylacrylamide, acrylic acid, and maleimide polyethylene glycol methacrylate is (88~92):(8~12):(1.5~3).
[0038] Example 3:
[0039] This embodiment differs from Example 1 in that the second component spinning solution is prepared by dissolving 92g of N-isopropylacrylamide, 12g of acrylic acid, and 3g of maleimide polyethylene glycol methacrylate in water, adding 1.07g of crosslinking agent N,N'-methylenebisacrylamide, 0.16g of initiator potassium persulfate, and 0.16g of sodium bisulfite, and stirring until homogeneous to obtain the second component spinning solution. The rest is the same as in Example 1.
[0040] Comparative Example 1 This comparative example uses commercially available LR calcium alginate silver fiber dressing Suprasorb A + Ag 10*10cm / piece.
[0041] Comparative Example 2 Based on Example 1, the difference is that the absorbent layer in this comparative example does not contain the second component fiber; the absorbent layer is prepared solely from the first component fiber. Everything else is the same as in Example 1.
[0042] Comparative Example 3 Based on Example 1, the difference from Example 1 is that the second component fiber of the absorbent layer in this comparative example does not contain maleimide polyethylene glycol methacrylate; otherwise, it is the same as Example 1.
[0043] Comparative Example 4 Based on Example 1, the difference from Example 1 is that the support layer of this comparative example uses a transparent polyurethane film backing of an existing dressing (3M TMTegaderm™ anti-liquidation film) instead of the support layer of Example 1; the rest is the same as Example 1.
[0044] Test Example 1: Water Vapor Transmission Rate Test Test solution: containing 142 mmol / L Na+ 2.5 mmol / L Ca 2+ Simulated wound exudate; Test method: Referring to the standard "Test methods for contact wound dressings - Part 2: Water vapor transmission rate of breathable membrane dressings" (YY / T 0471.2-2004), the water vapor transmission rate of the dressing samples of each example and comparative example before and after liquid absorption was tested, and the results are shown in Table 1; Method for detecting water vapor transmission rate before absorption: The dressing samples of each embodiment and comparative example (all sizes are 10cm×10cm, the size in the embodiments is based on the absorbent layer) were tested for water vapor transmission rate at 21℃ and 60%RH according to YY / T 0471.2-2004. The standard cup method was used, and WVTR1 (g / (m)) was recorded. 2 • 24h); Take another sample, and test the water vapor transmission rate of the dressing samples of each embodiment and comparative example (all sizes are 10cm×10cm, the size in the embodiments is based on the absorbent layer) according to YY / T0471.2-2004 at 37℃ and 60%RH. Use the standard cup method and record WVTR2 (g / (m 2 • 24h); 5 samples were tested in parallel for each group of samples, and the average value was taken; Method for detecting water vapor transmission rate after liquid absorption: The dressing samples (all 10cm × 10cm, with the dimensions in the examples based on the absorbent layer) of each embodiment and comparative example were immersed in simulated wound exudate at 37°C for 60 minutes to allow for full liquid absorption. After removal, the surface free water was gently absorbed with filter paper. The water vapor transmission rate was measured using the inverted cup method at 37°C and 60% relative humidity, and recorded as WVTR3 (g / (m²)). 2 • 24h); 5 samples were tested in parallel for each group of samples, and the average value was taken.
[0045] Table 1 Results of water vapor transmission rate test
[0046] Experimental Example 2: Time Detection of Liquid Leakage from Dressing Edges Device structure: A flat wound simulation base (made of polycarbonate) is placed in a 37℃ constant temperature chamber. The base has a simulated wound groove with a diameter of 5cm and a depth of 2mm in the center, and a liquid inlet hole at the bottom center of the groove. The simulated wound exudate (refer to test example 1) preheated to 37℃ in the simulated exudate storage bottle is passed sequentially through a peristaltic pump (flow rate 2.0 mL / h), a delivery pipeline, and from the liquid inlet hole at the bottom of the base from bottom to top into the wound groove, and comes into contact with the dressing absorbent layer. Test method: The absorbent inner surface of each embodiment and comparative dressing sample (refer to the size of Test Example 1) was placed face down on the groove of the flat wound simulation base, and the edges were fixed with pressure-sensitive adhesive; the peristaltic pump was started to supply liquid, and water-sensitive color-changing filter paper strips were placed at each edge of the dressing. The time from the start of the peristaltic pump to the first color change of the filter paper strip at the outer edge of the dressing (if the filter paper strip changes color on any side, it means that liquid is leaking from the edge of the dressing) was recorded as T leakage; the average value of 5 parallel samples was taken, and the results are shown in Table 2.
[0047] Table 2 Results of time-based detection of liquid seepage from dressing edges
[0048] Test Example 3: Other Performance Tests of Dressings The dressings prepared in Example 1, Comparative Example 2, and Comparative Example 3 were tested for absorbency, antibacterial activity, bacteriostatic properties, and biocompatibility over 30 minutes. The results are shown in Table 3.
[0049] 30-minute absorption rate: The absorption rate of the absorbent layer was tested. The absorbent layer samples of Example 1, Comparative Example 2, and Comparative Example 3 were prepared into 5cm×5cm sizes, weighed, and recorded as W_dry. They were then immersed in simulated wound exudate at 37°C (refer to Test Example 1) for 30 minutes, removed, hung to drain excess liquid, and weighed again. Absorption rate = (W_wet - W_dry) / W_dry × 100%. The average value of the three parallel samples was taken.
[0050] Antibacterial activity: Based on the silver ion antibacterial layer, 0.75g ± 0.05g of samples containing the silver ion antibacterial layer, absorbent layer, and support layer were cut from the dressings prepared in Example 1, Comparative Example 2, and Comparative Example 3 (the samples can be composed of multiple fragment structures containing the silver ion antibacterial layer, absorbent layer, and support layer). Standard strains of Escherichia coli, Staphylococcus aureus, and Candida albicans were selected according to GB / T 20944.3-2008 to prepare inoculation solutions. The samples were placed in Erlenmeyer flasks and shaken at 37℃ for 18h before the antibacterial rate was measured. The average value of the three parallel samples was taken.
[0051] Antibacterial properties: Refer to standard YY / T 0471.5-2017 "Test methods for contact wound dressings - Part 5: Antibacterial properties".
[0052] Biocompatibility: Cytotoxicity: Refer to standard GB / T 16886.5-2017 Biological evaluation of medical devices - Part 5: In vitro cytotoxicity tests; Skin sensitization / irritation: Refer to standard ISO 10993-10:2021 Biological evaluation of medical devices - Part 10: Skin sensitization tests and ISO 10993-23:2021 Biological evaluation of medical devices - Part 23: Irritation tests.
[0053] Table 3 Other performance tests of dressings
[0054] As described above, this application has good antibacterial, antimicrobial and biocompatibility properties, and compared with the prior art (Comparative Example 1), it can also have a moderate moisture permeability after absorbing liquid; compared with the prior art, it delays the time for the dressing to absorb liquid to the edge leakage liquid, and relatively improves the service time of the dressing in terms of liquid absorption.
[0055] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A hydrophilic fiber silver dressing, comprising, from the inside out, a silver ion antibacterial layer, an absorbent layer, and a support layer bonded together; the silver ion antibacterial layer is bonded to the center of the inner surface of the absorbent layer and the coverage area of the silver ion antibacterial layer is smaller than the inner surface area of the absorbent layer; the outer surface of the absorbent layer is bonded to the inner surface of the support layer, and the coverage area of the absorbent layer is smaller than the inner surface area of the support layer, characterized in that: The absorbent layer includes parallel bicomponent fibers, which include a first component fiber and a second component fiber arranged in parallel. The first component fiber includes thiolated calcium alginate; The second component fiber comprises a polymer obtained by polymerizing N-isopropylacrylamide, acrylic acid, and maleimide polyethylene glycol methacrylate; wherein the mass ratio of N-isopropylacrylamide, acrylic acid, and maleimide polyethylene glycol methacrylate is (88~92):(8~12):(1.5~3).
2. The hydrophilic fiber silver dressing according to claim 1, characterized in that: The silver ion antibacterial layer comprises the following components in parts by weight: 1-1.5 parts PVP-modified silver nanoparticles, 6-8 parts thiolated sodium alginate, 2-4 parts glycerol, and 88-90 parts deionized water; Among them, the PVP-modified silver nanoparticles are prepared by using PVP K30 and 0.05 M silver nitrate in a molar ratio of 2.5:1 as the main raw materials and ethylene glycol as the solvent at 80℃ to obtain PVP-modified silver nanoparticles with a particle size of 5~15nm. The mercaptomodified sodium alginate has a mercapto molar substitution degree of 20% and a purity of >95%.
3. The hydrophilic fiber silver dressing according to claim 1, characterized in that: The support layer comprises the following components in parts by weight: 100 parts of isocyanate-terminated polyurethane prepolymer and 15-20 parts of hydroxystearic acid modified attapulgite.
4. The hydrophilic fiber silver dressing according to claim 3, characterized in that: The isocyanate-terminated polyurethane prepolymer was prepared by reacting pure MDI and polycarbonate diol in a molar ratio of 2.2:
1. The hydroxystearic acid modified attapulgite was prepared by the following method: attapulgite was soaked in 5% HCl hydrochloric acid, stirred for 2 hours, centrifuged, washed until neutral, and dried to obtain acid-treated attapulgite; 100 parts of acid-treated attapulgite were dispersed in anhydrous ethanol, and 15 parts of 12-hydroxystearic acid and p-toluenesulfonic acid were added. The amount of p-toluenesulfonic acid added was 1% of the total mass of acid-treated attapulgite and hydroxystearic acid. The mixture was refluxed and stirred at 80°C for 4 hours. After filtration, washing, drying, and grinding, hydroxystearic acid modified attapulgite was obtained.
5. The hydrophilic fiber silver dressing according to claim 4, characterized in that: The support layer is prepared by the following method: 100 parts of isocyanate-terminated polyurethane prepolymer are dissolved in a mixed solvent of 300-400 parts DMF and 100-150 parts THF, 15-20 parts of hydroxystearic acid modified attapulgite and 0.05-0.1 parts of organic bismuth catalyst are added, and the mixture is stirred at high speed to disperse evenly. Vacuum degassing is then performed to obtain a spinning solution. The spinning solution is electrospun to obtain a fiber membrane. After the fiber membrane is cured by gradient heating, it is exposed to a water vapor environment with a relative humidity of 85%-90%, treated at 40°C for 1-2 hours, and then vacuum dried to obtain a support layer with a thickness of 30-40 μm. The gradient change of the fiber membrane during gradient heating curing is as follows: curing at 60℃ for 2 hours, then at 80℃ for 2 hours, and finally at 100℃ for 1 hour.
6. The hydrophilic fiber silver dressing according to claim 1, characterized in that: A pressure-sensitive adhesive layer is also provided on the inner surface of the support layer. The pressure-sensitive adhesive layer is uniformly distributed around the outer edge of the support layer, and the absorbent layer is surrounded inside the pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer is a medical-grade polyacrylate pressure-sensitive adhesive.
7. The hydrophilic fiber silver dressing according to claim 1, characterized in that: The cross-sectional area ratio of the first component fiber and the second component fiber is 45:
55.
8. A method for preparing a hydrophilic fiber silver dressing according to any one of claims 1-7, characterized in that: Includes the following steps: S1. Preparation of parallel bicomponent fibers: The first component spinning solution and the second component spinning solution are wet-spun through a parallel spinneret; the two spinning solutions converge and are extruded in parallel at the spinneret outlet, and the extruded fibers are solidified in a 3% calcium chloride aqueous solution coagulation bath at 50°C. After solidification, the fibers are stretched, washed with deionized water, and vacuum dried at 45°C to obtain parallel bicomponent fibers. The cross-sectional area ratio of the first component fiber to the second component fiber in the parallel bicomponent fibers is 45:
55. First component spinning solution: Dissolve sodium thiolated alginate with a thiol content of 500 μmol / g in water to prepare a sodium thiolated alginate solution with a mass fraction of 5%~7%, which is the first component spinning solution; The second component spinning solution: N-isopropylacrylamide, acrylic acid, and maleimide polyethylene glycol methacrylate are dissolved in water at a mass ratio of (88~92):(8~12):(1.5~3) to form a monomer reaction solution. N,N'-methylenebisacrylamide (a crosslinking agent) and potassium persulfate-sodium bisulfite (an initiator) are added to the monomer reaction solution to prepare the second component spinning solution. The amount of crosslinking agent is 1% of the total monomer mass, and the amount of initiator is 0.3% of the total monomer mass. S2. Process the parallel bicomponent fibers obtained in step S1 into fibers with a unit area mass of 100~120 g / m². 2 The nonwoven fabric forms an absorbent layer with a thickness of 0.25mm-0.35mm; S3. Preparation of silver ion antibacterial layer: Dissolve thiolated sodium alginate in deionized water, add glycerol and PVP-modified silver nanoparticles, mix evenly to obtain a dispersion; apply the dispersion to the central area of the inner surface of the absorbent layer in step S2 by spraying, and dry at 35°C in the dark to form silver ion antibacterial layer. S4. Composite the support layer and the absorbent layer: The outer surface of the absorbent layer with the silver ion antibacterial layer is bonded to the inner surface of the support layer by discrete dotted acrylic pressure-sensitive adhesive. The coverage area of the absorbent layer is smaller than the inner surface area of the support layer. After drying at 45°C for 30 minutes, it is die-cut, packaged and sterilized at low temperature with ethylene oxide to obtain the hydrophilic fiber silver dressing.
9. The method for preparing a hydrophilic fiber silver dressing according to claim 8, characterized in that, The silver content in a single hydrophilic fiber silver dressing is 0.08% of the total mass of the hydrophilic fiber silver dressing.
Citation Information
Patent Citations
Hemostatic sponge capable of rapidly expanding and preparation method thereof
CN117982716A
Fiber-reinforced hydrogel composites and methods of forming fiber-reinforced hydrogel composites
WO2013172788A1